The readiness of building information modeling (BIM) application in quantity surveying firm for quality improvement / Muhammad Syazwan Abdullah Sahaimi and Mohd Esham Mamat - Abdullah Sahaimi, Muhammad Syazwan; Mamat, Mohd Esham (2018)
Building Information Modelling (BIM) is a detailed process of designing and building in construction industry collaboratively by using one integrated system generated by computer rather than separating the work by distinguishing the drawings. On another hand, it provides a large amount of benefit in terms of cost saving and time, much better accuracy in estimation and reducing arithmetical error and any amendment due to loss of information. The main principle of this research is to investigate the readiness of BIM application in Quantity surveying firms for quality improvement especially in current practices. The objectives are to find out the importance of BIM in the construction industry, to investigate the challenges faces by quantity surveying firms in the implementation of BIM and to suggest a suitable solution for quality improvement to Quantity surveying firms. The data collection was conducted by using the quantitative method, which is using a questionnaire. The scope narrowed down to Quantity surveying firms that registered in the Board of quantity Surveyors Malaysia (BQSM) at Northern Region of Peninsular Malaysia only. The findings of the study are expected that Quantity surveying firms had difficulties in implement BIM because of lack capability in using BIM software. This is because of the complexity of software itself such as Cubicost by Glodon. Findings also indicate that difficulties of collaboration in implementing BIM software caused the firm to decline in using the software. Moreover, the implementation of BIM software also needed to join in by all parties that involved in the project such as architect and engineer. Hopefully, with this Research, the Quantity surveying firm will get clear exposure on the BIM application and use it in their current practices